Descriptive Analysis of Blood Pressure Changes Before and After Spinal Anesthesia in Patients with Respiratory System Comorbidities at Khidmad Sehat Afiat Regional General Hospital in 2023 - Nurdiani, Maria Delviana (West Science Interdisciplinary Studies, 2023)
Surgery using the Sectio caesarea (C-section) method is frequently performed on pregnant women, especially in Indonesia. Therefore, the Obstetric Anesthesia Guidelines recommend the use of spinal/epidural anesthesia techniques over general anesthesia for most C-section cases. However, this anesthesia procedure can induce changes in hemodynamic parameters, such as a decrease in blood pressure. To determine blood pressure changes before and after spinal anesthesia in patients undergoing C-section at RSUD Depok. This study is a qualitative descriptive case study using case analysis and cross-case analysis methods. Data collection was conducted using observation sheets as research instruments. Participants in this study consisted of two patients undergoing the C-section procedure. Findings from the study indicate that before the administration of spinal anesthesia, systolic blood pressure, diastolic blood pressure, and MAP were within the normal range. However, after spinal anesthesia administration, there was a decrease in systolic blood pressure, diastolic blood pressure, and MAP between the fifth and tenth minutes. This is associated with the onset time of the spinal anesthesia drug, which typically occurs within five to ten minutes after administration, and the typical effect of reducing blood pressure of the drug, especially in patients undergoing C-section at RSUD Depok. A decrease in blood pressure occurs after the administration of bupivacaine-type spinal anesthesia drug, with a dose of 0.5% bunascan 20 mg.